2016
DOI: 10.5146/tjpath.2015.01356
|View full text |Cite
|
Sign up to set email alerts
|

A six sigma trial for reduction of error rates in pathology laboratory

Abstract: Objective: A major target of quality assurance is the minimization of error rates in order to enhance patient safety. Six Sigma is a method targeting zero error (3.4 errors per million events) used in industry. The five main principles of Six Sigma are defining, measuring, analysis, improvement and control. Using this methodology, the causes of errors can be examined and process improvement strategies can be identified. The aim of our study was to evaluate the utility of Six Sigma methodology in error reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The A3 method is based on defining a problem, analyzing its causes, aiming at an ideal practice, and providing an improvement plan [9]. Other authors have also used industrial techniques, such as the Six Sigma, with excellent results in error reduction [16,38]. Examples of their measures were as follows: meetings with the clinical teams responsible for delivering the material to correct the inadequacy of the samples and intradepartmental meetings, in which employees actively participated in the discussions about the errors and their solutions.…”
Section: Looking For Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The A3 method is based on defining a problem, analyzing its causes, aiming at an ideal practice, and providing an improvement plan [9]. Other authors have also used industrial techniques, such as the Six Sigma, with excellent results in error reduction [16,38]. Examples of their measures were as follows: meetings with the clinical teams responsible for delivering the material to correct the inadequacy of the samples and intradepartmental meetings, in which employees actively participated in the discussions about the errors and their solutions.…”
Section: Looking For Solutionsmentioning
confidence: 99%
“…Of these, 88% (n = 432) of errors were found in the pre-analytical phase, in terms of the order, identification, collection, transportation, material reception, and processing in the laboratory. The authors identified 20% (n = 4) of analytical and 39% of (n = 8) post-analytical errors [15], as shown in Table 1, associated with Tosuner [16] survey data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical phase is reserved to microscopic evaluation of the slide and conceive the pathological report. Mistakes within this phase are encountered with a wide range of frequencies from 4 % (11) to 42.1% (6).…”
Section: The Analytical Phasementioning
confidence: 99%
“…Mistakes during tissue processing due to technical problems (power failure, incorrect was impregnation, different technical fault of automatic tissue processor or of cryostat, poor dehydration) Involving the patient Wrong identification data of the patient because of wrong labelling Mixing up the surgical probes Not having access to clinical data regarding the history of the patient or to different initial laboratory tests. Analytical phase (2,6,11,12) Intra-operative…”
Section: Identification Of Risks Exposurementioning
confidence: 99%